The role of optical coherence tomography in neuro-ophthalmology - Chen, John J.; Costello, Fiona (Annals of Eye Science; Vol 3 (June 2018): Annals of Eye Science, 2018)
Optical coherence tomography (OCT) is an ocular imaging technique that can complement the neuro-ophthalmic assessment, and inform our understanding regarding functional consequences of neuroaxonal injury in the afferent visual pathway. Indeed, OCT has emerged as a surrogate end-point in the diagnosis and follow up of several demyelinating syndromes of the central nervous system (CNS), including optic neuritis (ON) associated with: multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and anti-myelin oligodendrocyte glycoprotein (MOG) antibodies. Recent advancements in enhanced depth imaging (EDI) OCT have distinguished this technique as a new gold standard in the diagnosis of optic disc drusen (ODD). Moreover, OCT may enhance our ability to distinguish cases of papilledema from pseudopapilledema caused by ODD. In the setting of idiopathic intracranial hypertension (IIH), OCT has shown benefit in tracking responses to treatment, with respect to reduced retinal nerve fiber layer (RNFL) measures and morphological changes in the angling of Bruch’s membrane. Longitudinal follow up of OCT measured ganglion cell-inner plexiform layer thickness may be of particular value in managing IIH patients who have secondary optic atrophy. Causes of compressive optic neuropathies may be readily diagnosed with OCT, even in the absence of overt visual field defects. Furthermore, OCT values may offer some prognostic value in predicting post-operative outcomes in these patients. Finally, OCT can be indispensable in differentiating optic neuropathies from retinal diseases in patients presenting with vision loss, and an unrevealing fundus examination. In this review, our over-arching goal is to highlight the potential role of OCT, as an ancillary investigation, in the diagnosis and management of various optic nerve disorders.